Effectiveness of public expenditure in correcting the Imbalance of Trade Structure in Iraq after year 2003 - صالح لورنس يحيى; عداي نور شدهان (Journal of Economics and Administrative Sciences, 2020)
This research aims to focus on the reality of the imbalance of the balance of trade structure in order to improve it and determine the size of the imbalance as a result of dependence on one commodity, namely crude oil in the structure of exports versus the diversity of the structure of imports of various goods and goods. In order to achieve that goal, a deductive approach was adopted, which included a shift from general theory data to special applications. We have reached through the research to a number of conclusions, most notably the effectiveness of public spending in correcting the imbalance of the balance of trade structure during the study period, despite the increase in trends, and this is due to the predominance of consumer spending on investment spending and the almost complete cessation of the productive apparatus. Based on this, the research Recommends a necessity restructuring public spending by increasing investment spending allocations in parallel with current spending, thereby reducing the disparity between them.